Neighborhood Poverty, College Attendance, and Diverging Profiles of Substance Use and Allostatic Load in Rural African American Youth - Chen, Edith (Clin Psychol Sci, 2014)
A subset of African American youth who live in impoverished neighborhoods display resilient profiles academically and behaviorally. We hypothesized that this resilience might be “skin-deep,” in that the ongoing efforts needed to achieve success might take a physiological toll on these youth. At age 19, 452 rural African American youth were assessed on broader contextual risk (neighborhood poverty) and external indicators of success (college attendance). One year later, participants were assessed on substance use and cumulative physiological risk (allostatic load). African American youth from more disadvantaged neighborhoods who attended college had lower levels of substance use, but higher levels of allostatic load compared to those from less disadvantaged neighborhoods who attended college, or to those who did not attend college. These findings indicate that a subset of African American youth from poor neighborhoods exhibits a profile of “skin-deep resilience,” characterized by external successes combined with heightened internal physiological risk.